Religious Affiliation and Marital Satisfaction: Commonalities Among Christians, Muslims, and Atheists - Sorokowski, Piotr; Kowal, Marta; Sorokowska, Agnieszka (Frontiers in Psychology, 2019)
Scientists have long been interested in the relationship between religion and numerous aspects of people’s lives, such as marriage. This is because religion may differently influence one’s level of happiness. Some studies have suggested that Christians have greater marital satisfaction, while others have found evidence that Muslims are more satisfied. Additionally, less-religious people have shown the least marital satisfaction. In the present study, we examined marital satisfaction among both sexes, and among Muslims, Christians, and atheists, using a large, cross-cultural sample from the dataset in Sorokowski et al. (2017). Our results show that men have higher marital satisfaction ratings than women, and that levels of satisfaction do not differ notably among Muslims, Christians, and atheists. We discuss our findings in the context of previous research on the association between marriage and religion.